Hubungan Dukungan Keluarga Dengan Self-Care Management Pasien Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Galesong - Nur Anbiya; Susi Susanti; Ayatullah (2024)
This study aims to analyze the relationship between family support and self-care management of type 2 diabetes mellitus patients in the Galesong Health Center Working Area, Galesong District, Takalar Regency. The research method used is quantitative with a cross sectional design. The population in this study were Type 2 DM patients in January-December 2023. The sample technique used was purposive sampling, so that the number of samples in this study was 84 samples. Data were collected through a questionnaire that had been tested for validity and reliability, then analyzed using the chi-square test. The results showed that there was a relationship between family support and self-care management of type 2 diabetes mellitus patients in the Galesong Health Center Working Area, Galesong District, Takalar Regency. However, it is expected that families of patients with Type 2 DM who are still lacking in support to better understand the patient's self-care needs. So it is hoped that the number of DM patients who have a low level of self-care management can be reduced.